What kinds of learning srategis tend to facilitate learning among adult students in higher education / Jelani Sulaiman - Sulaiman, Jelani (Universiti Teknologi MARA Cawangan Pahang, 1995)
The primary purpose of this paper is to examine several learning strategies which could be utilized in facilitating learning among adult students in higher education. Several sociological and psychological characteristics of adult learners. their teaching preferences. and aspects of learning and memory as well as motivation in adult education are discussed. These characteristics are then considered and integrated into the methods and techniques or adult teaching and learning. Recommendation are put forward for learning strategies which would facilitate learning among adult learners.